New Ways to Calculate the Probability in the Bertrand Problem - Rodrigo Hitos, Javier; López-González, Mariló; Lantarón Sánchez, Sagrario (My University, 2023)
.

We give two new ways of calculating the probability of a chord of circumference randomly selected being larger than the side of an equilateral triangle inscribed in the circumference (this problem is known as the Bertrand paradox). The first one employs an immersion in R4, and the second one uses a direct probability measure over the set of chords.
Artículos en revistas